SINERGI EFISIENSI DAN ETIKA: MEMBANGUN KERANGKA KERJA OPERASIONAL BERBASIS LEAN DAN MAQASHID SYARIAH - Jazlynne Attia Pradnya Ubaedi; Hanif Yasir; Ilham Syuhada Amaanullah (Taksasila Edukasi Insani, 2026)
This conceptual paper addresses the critical gap between the global demand for operational efficiency and the increasing need for value-based, ethically guided business practices, particularly within the context of the Indonesian Halal industry. The study aims to formulate a integrating Lean Management principles with the goals of Maqashid Syariah. Employing a theoretical synthesis method based on an analytical review of Indonesian scholarly literature published between 2021 and 2025, the research establishes a robust conceptual synergy. The findings demonstrate that Lean methodologies serve as the precise operational mechanism for achieving the ethical objectives of Syariah. Specifically, the elimination of waste (Muda) directly supports Hifz al-Mal (protection of wealth) by preventing Tabzir (extravagance), while the Lean philosophy of Respect for People aligns with Hifz al-Nafs (protection of life/welfare). Furthermore, the core principle of continuous improvement (Kaizen) finds its spiritual anchor in the Islamic ethos of Ihsan and Itqan (professional excellence). This framework posits that Maqashid Syariah must function as the comprehensive governance pillar guiding all operational decisions, ensuring that efficiency efforts lead to widespread Maslahah (public welfare). The primary contribution is a sustainable, ethical model of Operational Excellence that necessitates a new system of measurement, the Maslahah Index, to track both economic productivity and moral accountability.Keywords : Lean Management, Maqashid Syariah, Operational Excellence, Maslahah, Kaizen, Hifz al-Mal, Conceptual Framework